The Lithuanian Stroke Database: selection of national stroke care performance measures - Dapkutė, Austėja; Trinkūnas, Justas; Rastenytė, Daiva; Matijošaitis, Vaidas; Taroza, Saulius; Jatužis, Dalius; Baužaitė-Babušienė, Sandra; Vilionskis, Aleksandras; Klimašauskas, Andrius; Juodakis, Julius; Jaramavičius, Julius; Masiliūnas, Rytis (Frontiers in Neurology, 2025)
IntroductionThe Lithuanian Stroke Database (StrokeLT) aims to automate data collection and key performance indicator (KPI) monitoring across all stroke-ready hospitals, addressing the limitations of manual processes and facilitating evidence-based improvements in stroke care nationwide. This publication outlines the selection process and target values of the KPIs designed to standardise and enhance stroke care quality in Lithuania.Study populationThe database will include all adult patients diagnosed with stroke or transient ischemic attack (TIA), admitted to Lithuanian stroke-ready hospitals, encompassing approximately 9,582 annual stroke and 1,899 TIA admissions based on 2023 data. The database will ensure comprehensive national coverage by integrating data from stroke centres via a centralised electronic health record system.Main variablesA total of 53 KPIs were selected through a multi-stage Delphi process involving national experts and guided by international standards. These KPIs include 44 process metrics, such as timeliness metrics, early rehabilitation, and availability of secondary prevention, as well as 8 outcome metrics, including functional recovery, completion of a patient feedback survey and mortality. This framework enables comprehensive monitoring across all stages of patient care, as well as incorporating valuable patient feedback.ConclusionThe Lithuanian Stroke Database establishes a standardised automated framework for monitoring stroke care using 53 KPIs, selected through a multi-stage Delphi process involving all relevant stakeholders.